Blanching alters the phenolic constituents and in vitro antioxidant and anticholinesterases properties of fireweed (Crassocephalum crepidioides). Issue 4 (December 2015) - Adedayo, Bukola C.; Oboh, Ganiyu; Oyeleye, Sunday I.; Ejakpovi, Isaac I.; Boligon, Aline A.; Athayde, Margareth L.
الملخص: أهداف البحث: يحقق هذا البحث في تأثير الإبيضاض على توزيع الفينول وخصائص مضادات الأكسدة ومضادات الكولينستراز في المختبر لمستخلصات ميثانوليك- حمض الهيدروكلوريك المستخرجة من العشبة. طرق البحث: تم تحضير المستخلصات الغنية بالفينول باستخراج أوراق العشبة المجففة المبيضة وغير المبيضة مع مزيج ثابت ١ م من حمض الهيدروكلوريك وميثانول (١:١). تم تحليل المكونات الفينولية باستخدام كروماتوجرافيا عالية الأداء مقرونة مع كاشف المجموعة ثنائي الصمام. علاوة على ذلك٬ تم تحديد مضادات الأكسدة مخبريا ((خصائص جذور الكسح وقدرات الحديد الخالبة وكبت الحديد التي يسببها بيروكسيد الدهون في دماغ الفأر المعزول] وتم تحديد تأثير كبت مستخلصات اسيتايل كولينستراز وبيوتريكولينستراز مخبريا. النتائج: كشفت التحاليل المخبرية عن أربعة من الأحماض الفينولية وثلاثة من مركبات الفلافونويدز المتوفرة بكثرة في المستخلصات غير المبيضة من العشبة. وأظهرت النتائج أيضا أن المستخلصات غير المبيضة من العشبة لها خصائص عالية كمضادات أكسدة وخصائص اسيتايل كولينستراز وبيوتريكولينستراز مثبطة بالمقارنة بالعشبة المبيضة. الاستنتاجات: الخصائص العالية كمضادات للأكسدة ومضادات الكولينستراز لمستخلصات العشبة غير المبيضة ممكن أن ترتبط بمكوناتها العالية من الفينول بالمقارنة بالعشبة المبيضة. عليه٬ يؤدي الإبيضاض إلى نقص الخصائص كمضادات للأكسدة ومضادات الكولينستراز للعشبة والبرهان على ذلك انخفاض خسارة محتويات الفينول من العشبة المبيضة. Abstract: Objective: This research investigated the effect of blanching on the phenolic distribution and in vitro antioxidant and anticholinesterase properties of the HCl-methanolic extracts from fireweed. Methods: Phenolic-rich extracts were prepared by extracting the powdered blanched and unblanched fireweed leaves with a mixture of absolute 1 M HCl and methanol (1:1 v/v). The phenolic constituents were analysed using high-performance chromatography coupled to a diode array detector (HPLC-DAD). Furthermore, the extracts' in vitro antioxidant [1, 1-diphenyl-2-picrylhydrazyl (DPPH), 2, 2-azinobis(3-ethylbenzo-thiazoline-6-sulfonate (ABTS) radical scavenging and Fe 2+ chelating abilities and inhibition of Fe 2+ -induced lipid peroxidation in isolated rat brain] properties and inhibitory effects against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) were determined in vitro . Results: The HPLC-DAD analysis detected four phenolic acids (gallic, chlorogenic, caffeic and ellagic acids) and three flavonoids (catechin, rutin and quercetin) that were abundant in the unblanched fireweed extract. The findings further showed that the unblanched fireweed extract had higher antioxidant and AChE and BChE inhibitory properties compared to the blanched fireweed extract. Conclusion: The increased antioxidant and anticholinesterase properties of the unblanched fireweed extract could be linked to its higher concentrations of the phenolic constituents compared to the blanched firewood. Therefore, blanching leads to a decrease in the antioxidant and anticholinesterase properties of fireweed, as evidenced by a reduction/loss in the polyphenolic content from the blanched fireweed.